Carbon Footprint Report 2023 (European Investment Bank, 2025)
This report offers a detailed analysis of the European Investment Bank Group’s greenhouse gas emissions from its head office operations in Luxembourg for 2023. It includes a comparative performance review against 2022 and the baseline year of 2018, based on data adhering to the World Resources Institute Greenhouse Gas Protocol. The report highlights both gross and net emissions, with a primary focus on net emissions, categorising renewable energy consumption as zero direct emissions. It also details the methodology improvements and boundary expansions made in 2023, leading to a restatement of the previous year’s emissions without altering the baseline targets. Appendices I and II provide further insights into these changes and their impacts.